2020
DOI: 10.1159/000507444
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Adult Rhinitis for Multimorbidity and Age at Onset among Non-Sensitized Rhinitis and Mono-/Poly-Sensitized Rhinitis: A Retrospective Cross-Sectional Study

Abstract: Background: Recent studies have proposed that clinical and immunological differences exist between mono- and poly-sensitized subjects with allergic diseases, and poly-sensitization was related to multimorbidity of allergic diseases among children and adolescents. Objective: We compared the clinical characteristics and multimorbidity of allergic diseases between adult rhinitis patients mono- and poly-sensitized to common aeroallergens using a retrospective cross-sectional study for tertiary care subjects. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The increased risk of AR in patients with AD has been seen in multiple studies using different research strategies (i.e., prospective, population‐based, cross‐sectional) in different age groups and in different continents (Asia, Europe). This supports the notion that AR and AD are related diseases 739,2854,3055–3064 …”
Section: Associated Conditionssupporting
confidence: 87%
See 2 more Smart Citations
“…The increased risk of AR in patients with AD has been seen in multiple studies using different research strategies (i.e., prospective, population‐based, cross‐sectional) in different age groups and in different continents (Asia, Europe). This supports the notion that AR and AD are related diseases 739,2854,3055–3064 …”
Section: Associated Conditionssupporting
confidence: 87%
“…In one study, for example, less than half of all patients reporting AR had a physician‐confirmed diagnosis of AR 3054 . Therefore, the link between AR and AD remains poorly defined due to methodologic differences and limitations of the studies that have examined this association 739,2854,3055–3065 (Table XIII.D).…”
Section: Associated Conditionsmentioning
confidence: 99%
See 1 more Smart Citation